Analysis of Drug Management and Improvement Strategies Using the Hanlon Method in Pharmaceutical Installations RSUD Dr. Moewardi in 2022 - Sakaria, Hamra; Wijayanti, Tri; Dewi, Lucia Vita Inandha (Jurnal Multidisiplin Madani, 2024)
Drug management at RSUD Dr.Moewardi in previous research showed that drug management in the Pharmacy Installation at Dr. Moewardi is not yet efficient. Dr. Moewardi Hospital Pharmacy Installation which includes the selection, planning, procurement, distribution and use stages in 2022, determine priority drug management problems based on the Hanlon method and find out strategies for improving drug management in the RSUD Pharmacy Installation Dr.Moewardi in 2022. Secondary data was obtained from interviews with the Head of the Pharmacy Installation at RSUD Dr. Moewardi. The results of research on drug management at IFRSUD Dr. Moewardi who did not meet the standards at the selection stage for suitability of drug items available at Fornas (82.80%) and FRS (81.41%) at the procurement stage, percentage of drug procurement fund allocation (17.27%) Frequency of late payments (448X) percentage of suitability of drug planning(87.16%) at the distribution stage accuracy of drug quantity data on stock cards (95%) ITOR(15.078 times) percentage of expired drugs (0.04%), percentage of dead stock (13%) and at the usage stage the number of drug items per prescription sheet (3.6), the percentage of generic drug use (72.85%) and the average waiting time for compounded drugs was (61.76 minutes) and non-mixed (28.68 minutes)